2019
DOI: 10.3389/fendo.2019.00807
|View full text |Cite
|
Sign up to set email alerts
|

Use of Mendelian Randomization to Examine Causal Inference in Osteoporosis

Abstract: Epidemiological studies have identified many risk factors for osteoporosis, however it is unclear whether these observational associations reflect true causal effects, or the effects of latent confounding or reverse causality. Mendelian randomization (MR) enables causal relationships to be evaluated, by examining the relationship between genetic susceptibility to the risk factor in question, and the disease outcome of interest. This has been facilitated by the development of two-sample MR analysis, where the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 77 publications
0
25
0
Order By: Relevance
“…Among adults, a small male predominance of HPI-related outcomes has been found in a meta-analysis based on 169 studies (OR 1.12, 95% CI: 1.09, 1.15) [ 407 ]. Shared genetic basis underlying OP and a variety of HPI-related chronic extra-gastroduodenal diseases (CAD, DM, dyslipidemia) has been reported [ 408 , 409 , 410 , 411 , 412 , 413 , 414 , 415 , 416 , 417 , 418 , 419 ]. The shared biology and bi-(multi-)directional links between OP and HPI-associated chronic diseases apply particularly to CVD, CKD, CLD, DM and neurodegenerative diseases; these disorders are interrelated and often accompanied by OP/OF [ 420 , 421 , 422 , 423 , 424 , 425 , 426 , 427 , 428 , 429 , 430 ], and the risk of OP/OF increases when two or more HPI-associated chronic diseases are present.…”
Section: Hpi-associated Chronic Extra-gastroduodenal Diseases Medmentioning
confidence: 99%
See 1 more Smart Citation
“…Among adults, a small male predominance of HPI-related outcomes has been found in a meta-analysis based on 169 studies (OR 1.12, 95% CI: 1.09, 1.15) [ 407 ]. Shared genetic basis underlying OP and a variety of HPI-related chronic extra-gastroduodenal diseases (CAD, DM, dyslipidemia) has been reported [ 408 , 409 , 410 , 411 , 412 , 413 , 414 , 415 , 416 , 417 , 418 , 419 ]. The shared biology and bi-(multi-)directional links between OP and HPI-associated chronic diseases apply particularly to CVD, CKD, CLD, DM and neurodegenerative diseases; these disorders are interrelated and often accompanied by OP/OF [ 420 , 421 , 422 , 423 , 424 , 425 , 426 , 427 , 428 , 429 , 430 ], and the risk of OP/OF increases when two or more HPI-associated chronic diseases are present.…”
Section: Hpi-associated Chronic Extra-gastroduodenal Diseases Medmentioning
confidence: 99%
“…Notes: Recent genetic studies have challenged some long-assumed risk factors for OP/OF. Mendelian randomization analyses identified BMD [ 413 , 635 , 636 , 637 ], serum estradiol concentrations (in men) [ 638 ] and cigarette smoking [ 639 ] as causal risk factors for OP/OFs, whereas genetic predisposition to lower levels of vitamin D and milk calcium intake [ 635 , 636 , 639 , 640 ], serum testosterone [ 638 ] and inflammation markers [ 641 , 642 ], as well as early menopause; late puberty, chronic (including CVD, DM and IBD) [ 413 , 414 , 643 ] and neuropsychiatric diseases (Alzheimer’s disease, schizophrenia and bipolar disorder) [ 644 ], alcohol consumption [ 645 ] and alcohol dependence [ 639 ] did not show causal effects on BMD and fracture risk. The genetic studies overcome many limitations of the previous observational studies but also contain potential bias; “the Mendelian randomization study design cannot be used to assess whether complications or treatment of those diseases influence fracture risk” [ 636 ].…”
Section: Figurementioning
confidence: 99%
“…One option to determine whether or not a causal association between sleep and pain is the Mendelian randomization (MR) analysis, which use single nucleotide polymorphisms (SNPs) in individuals as instrumental variables to examine the evidence for causal relationships between a trait and a disease [ 17 , 19 ]. MR was originally developed as a “one-sample” based analysis, relying on individual-level data, which are generally more difficult to utilize for researchers and are not used for multiple GWASs [ 20 ]. Thus, as the SNPs associated with exposure risk traits and outcome diseases or conditions are often found in different GWASs, the two-sample MR method has been developed.…”
Section: Introductionmentioning
confidence: 99%
“…The use of the MR approach in the field of osteoporosis has provided remarkable insight when scrutinizing the main clinical risk factors of fracture risk. A plethora of risk factors for osteoporosis identified by observational studies have been tested using MR [reviewed by us and others elsewhere ( 77 , 78 )]. Trajanoska et al ( 79 ) showed that BMD is the most important “causally-related” determinant of fracture risk; and that prevention strategies aimed at increasing or maintaining BMD are the most likely to be successful, in contrast to strategies targeting the other traditionally used risk factors.…”
Section: What Have We Learned From Complex Skeletal Traits?mentioning
confidence: 99%